2014
DOI: 10.1037/xlm0000020
|View full text |Cite
|
Sign up to set email alerts
|

Older adults do not notice their names: A new twist to a classic attention task.

Abstract: Although older adults have lower working memory spans on average than young adults, we demonstrate in five experiments one way in which older adults paradoxically resemble higher-capacity young adults. Specifically, in a selective-listening task, older adults almost always failed to notice their names presented in an unattended channel. This is an exaggeration of what high-span young adults show, and the opposite of what low spans show. This striking finding in older adults remained significant after controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 47 publications
(56 reference statements)
2
35
0
Order By: Relevance
“…Supporting this perspective, others have also observed that the level of processing applied to task-irrelevant stimuli can be affected by task demands ( Hohlfeld and Sommer, 2005 ; Pulvermüller et al, 2008 ). Moreover, individual differences in attentional abilities, and particularly the ability to process concurrent speech, have been attributed partially to working-memory capacity, a trait associated with the availability of more cognitive resources ( Beaman et al, 2007 ; Forster and Lavie, 2008 ; Naveh-Benjamin et al, 2014 ; Lambez et al, 2020 ) but cf. ( Elliott and Briganti, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this perspective, others have also observed that the level of processing applied to task-irrelevant stimuli can be affected by task demands ( Hohlfeld and Sommer, 2005 ; Pulvermüller et al, 2008 ). Moreover, individual differences in attentional abilities, and particularly the ability to process concurrent speech, have been attributed partially to working-memory capacity, a trait associated with the availability of more cognitive resources ( Beaman et al, 2007 ; Forster and Lavie, 2008 ; Naveh-Benjamin et al, 2014 ; Lambez et al, 2020 ) but cf. ( Elliott and Briganti, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study set, we did not collect additional personal data from participants which may have shed light on the source of the observed variability in gaze-patterns across individuals. However, based on previous literature, individual differences may stem from factors such as susceptibility to distraction (Ellermeier and Zimmer, 1997; Cowan et al, 2005; Avisar and Shalev, 2011; Bourel-Ponchel et al, 2011; Forster and Lavie, 2014; Hughes, 2014), working memory capacity (Conway et al, 2001; Kane and Engle, 2002; Tsuchida et al, 2012; Sörqvist et al, 2013; Hughes, 2014; Naveh-Benjamin et al, 2014; Wiemers and Redick, 2018) or personality traits (Rauthmann et al, 2012; Risko et al, 2012; Baranes et al, 2015; Hoppe et al, 2018). Additional dedicated research is needed to resolve the source of the individual differences observed here.…”
Section: Discussionmentioning
confidence: 99%
“…N. Cowan was added to the collaboration because he had another relevant theory and was already working with R. H. Logie on several related projects, despite holding different views (a special journal issue on working memory introduced by Logie and Cowan, 2015, and a dissertation committee resulting in joint publications, Rhodes, Cowan, Hardman, & Logie, 2018; Rhodes, Cowan, Parra, & Logie, 2019; Rhodes, Parra, Cowan, & Logie, 2017). M. Naveh-Benjamin, who has worked with N. Cowan on working memory and aging (e.g., Cowan, Naveh-Benjamin, Kilb, & Saults, 2006; Gilchrist, Cowan, & Naveh-Benjamin, 2008; Naveh-Benjamin et al, 2014), was included on the grant proposal to help us enrich our comparison of the theories via research on cognitive aging.…”
Section: Our Extended Adversarial Collaboration On Working Memorymentioning
confidence: 99%